Andorra : Assessment of Financial Sector Supervision and Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the assessment of Financial Sector Supervision and Regulation in Andorra. The assessment reveals that bank supervision in Andorra is broadly sound and has improved since the 2002 assessment. Institut Nacional Andorra de Finances' (INAF) new charter strengthened its independence and remedial powers. But these could be further strengthened by empowering it to impose all types of sanctions. Developing INAF's onsite supervisory capacity and clarifying its requests to external auditors will be important for the bank and nonbank financial sectors.